Pengelolaan Perencanaan Proyek E-Business - Yohanes Suhari (Universitas Stikubank, 2002)
In today's fast growing demand of electronic transactions, with more people accessing the internet worldwide, online shopping becomes an increasingly profitable but risk, business. Selling online becomes a very competitive business and time is a critical factor in launching a web site for business. This paper studies the strategic planning process of an electronic business project and identifies how risks can be minimized by proper planning and how planning is implemented. It also describes how to detect any changes in the marketplace so that effective measures, can be made to avoid dropping out from competitor. The emphasis is on the planning tactics, particularly in ensuring accurate tracking that is specific to the e-business start up process.